The Role of MicroRNAs in Endothelial Cell Senescence - Jovana Nikolajevic; Nazila Ariaee; Aaron Liew; Shadi Abbasnia; Bahare Fazeli; Miso Sabovic (Cells, 2022)
Cellular senescence is a complex, dynamic process consisting of the irreversible arrest of growth and gradual deterioration of cellular function. Endothelial senescence affects the cell’s ability to repair itself, which is essential for maintaining vascular integrity and leads to the development of endothelial dysfunction, which has an important role in the pathogenesis of cardiovascular diseases. Senescent endothelial cells develop a particular, senescence-associated secretory phenotype (SASP) that detrimentally affects both surrounding and distant endothelial cells, thereby facilitating the ageing process and development of age-related disorders. Recent studies highlight the role of endothelial senescence and its dysfunction in the pathophysiology of several age-related diseases. MicroRNAs are small noncoding RNAs that have an important role in the regulation of gene expression at the posttranscriptional level. Recently, it has been discovered that miRNAs could importantly contribute to endothelial cell senescence. Overall, the research focus has been shifting to new potential mechanisms and targets to understand and prevent the structural and functional changes in ageing senescent endothelial cells in order to prevent the development and limit the progression of the wide spectrum of age-related diseases. The aim of this review is to provide some insight into the most important pathways involved in the modulation of endothelial senescence and to reveal the specific roles of several miRNAs involved in this complex process. Better understanding of miRNA’s role in endothelial senescence could lead to new approaches for prevention and possibly also for the treatment of endothelial cells ageing and associated age-related diseases.